Sonography, Color Doppler And Power Doppler Evaluation of Palpable Breast Masses With Pathological Correlation - Jain, Soumya; Phatak, Suresh Vasant (International Journal of Psychosocial Rehabilitation, 2020)
Background: Breast ultrasound is used for the diagnosis and evaluation of various breast lesions. The application of Doppler sonography to the study of breast nodules provides a method by which the presence or absence of neovascularity can be detected. Color and Power Doppler along with ultrasonography has increased the diagnostic accuracy and This can in turn reduce the need for unnecessary biopsies of benign lesions. Objectives- To study Ultrasound features, Color Doppler and Power Doppler flow patterns in various benign and malignant breast lesions and to use the flow patterns in differentiating malignant breast lesions from benign. Compare Ultrasound and Doppler imaging findings with pathological diagnosis which is the gold standard Methodology -The prospective cross sectional study will be done in the department Radiodiagnosis, Jawaharlal Nehru Medical College , Sawangi (Meghe) for a period of 2 years for patients coming with clinically suspected palpable breast lesions .After giving informed consent, patients will undergo history recording and sonography, color Doppler and Power Doppler evaluation of the palpable breast mass using Aloka Hitachi USG machine Arietta S70 will be made. This Ultrasonography and Doppler findings will be later confirmed with Pathological reports. Result. After appropriate statistical analysis we expect a suspicious malignant mass to appear “taller than wider” with posterior acoustic shadowing on ultrasonography with high vascularity , a RI>0.65 and PI >1.6 with central or penetrating vessels on doppler. A benign palpable mass will include a “wider than taller" lesion, homogeneous in echotexture with benign doppler features such a Low RI and peripheral vessels .Conclusion. Sonography, Color Doppler and Power Doppler can help in differentiating malignant lesions from benign at an earliest possible stage and keep unnecessary biopsies to a bare minimum and detect early stages of breast cancer which can alter disease progression and therefore prognosis post-treatment. Keywords -Breast, Doppler, Malignant, Benign.